Effects of chitosan coatings on physicochemical and nutritional quality of clementine mandarins cv. 'Oronules' - Contreras-Oliva, Adriana; Pérez-Gago, María B.; Rojas-Argudo, Cristina (2017)
A commercial solution of chitosan was applied on mandarins 'Oronules' at different solid content (0.6%, 1.2% and 1.8%). Additionally, one group of mandarins was coated with a polyethylene-shellac commercial wax, and another group remained uncoated (control). Mandarins were stored at 5 degrees C up to 28 days followed by 7 days at 20 degrees C simulating retail conditions. One group of mandarins was stored at 20 degrees C for 9 days simulating direct retail conditions. The commercial wax decreased weight and firmness loss of mandarins compared to uncoated samples, whereas the chitosan coating did not effectively decrease weight loss of mandarins. Chitosan-coated mandarins at the highest solid content retained firmness after cold storage and contained more phenolics than uncoated ones. Although all the coatings restricted gas exchange and modified the internal atmosphere of the mandarins, with a greater effect at higher chitosan concentration, sensory quality was not affected. In general, the internal quality and the health-related properties of mandarins were not negatively affected by coating application. However, there is a need to further improve the water barrier properties of the chitosan coating.